Reviews of recent publications (Studies in 20th & 21st Century Literature, 1994)
Bjornson, Richard. The African Quest for Freedom and Identity: Cameroonian Writing and the National Experience by Thomas A. Hale Cixous, Hélène. 'Coming to Wrting' and Other Essays by Randi Brox Birn Derwin, Susan. The Ambivalence of Form: Lukacs, Freud, and the Novel by Eva L. Corredor Kaminsky, Amy K. Reading the Body Politic: Feminist Criticism and Latin American Women Writers by Naomi Lindstrom Nägele, Rainer. Theater, Theory, Speculation: Walter Benjamin and the Scenes of Modernity by Alice A. Kuzniar Tomlinson, John. Cultural Imperialism by Michael Filcher Weisberg, Richard. Poethics and Other Strategies of Law and Literature by Sara B. Blair
Keywords: Richard Bjornson; The African Quest for Freedom and Identity: Cameroonian Writing and the National Experience; Hélène Cixous; ' Coming to Writing' and Other Essays; Susan Derwin; The Ambivalence of Form: Lukacs Freud and the Novel; Amy K. Kaminsky; Reading the Body Politic: Feminist Criticism and Latin American Women Writers; Rainer Nägele; Theater Theory Speculation: Walter Benjamin and the Scenes of Modernity; John Tomlinson; Cultural Imperialism; Richard Weisberg; Poethics and Other Strategies of Law and Literature; Thomas A. Hale; Randi Brox Birn; Eva L. Corredor; Naomi Lindstrom; Alice A. Kuzniar; Michael Filcher; Sara B. Blair